(untitled) (International journal of medical sciences, 2026)
Language serves not only as a means of communication among the peoples of the world, but also as a medium for culture, science, diplomacy, and the exchange of knowledge. Therefore, in foreign language education, it is essential that teachers possess comprehensive linguistic competence and the ability to compare meanings, structures, and cultural elements between the native language and the target language. A deep understanding of both linguistic and cultural dimensions is crucial for effective translation and communication.